Genetic abnormalities in adolescents and young adults with neuroblastoma: A report from the Italian Neuroblastoma group. Issue 10 (29th April 2015) - Mazzocco, Katia; Defferrari, Raffaella; Sementa, Angela Rita; Garaventa, Alberto; Longo, Luca; De Mariano, Marilena; Esposito, Maria Rosaria; Negri, Francesca; Ircolò, Davide; Viscardi, Elisabetta; Luksch, Roberto; D'Angelo, Paolo; et al.
<x xml:space="preserve">Abstract</x> Background Less than 5% of neuroblastomas (NB) occur in adolescents and young adults (AYA), in whom the disease has an indolent and fatal course. Procedure We studied the genomic profile and histological characteristics of 34 NBs from AYA patients enrolled in the Italian Neuroblastoma Registry (INBR) between 1979 and 2009. Results Disease was disseminated in 20 patients and localized in 14; 30/34 tumors were classified as NB and 4/34 as nodular ganglioneuroblastoma (nGNB). Segmental Chromosome Aberrations (SCAs) were observed in 29 tumors (85%) namely 1p imbalance (58%), 17q gain (52%), 9p loss (32%), 11q loss (30%), 1q gain (17%), 7q gain (17%), 2p gain (14%), 3p loss (14%), and 4p loss (7%). MYCN amplification and MYCN gain were detected in 3 (10%) and 2 cases (7%) respectively. An anaplastic lymphoma receptor tyrosine kinase (ALK) gene mutation study on the available cases from this cohort revealed 4/25 (16%) mutated cases. In parallel, alpha thalassaemia/mental retardation syndrome X linked (ATRX) gene mutations were also sought, a novel mutation being detected in 1/21 (4, 7%) cases. Conclusion This study confirmed the low incidence of MYCN amplification in AYA and recorded a high frequency of 17q gain and 9p and 11q loss independently from the stage of the disease. The presence of 1q gain, which identifies patients with particularly aggressive disease, relapse and poor survival, was also detected. Furthermore, the frequency of ALK mutations suggests that a target‐based therapy with ALK inhibitors might be effective in this subset of patients. Pediatr Blood Cancer 2015;62:1725–1732. © 2015 Wiley Periodicals, Inc.